2016
DOI: 10.1177/0956797616645096
|View full text |Cite
|
Sign up to set email alerts
|

The Missing-Phoneme Effect in Aural Prose Comprehension

Abstract: When participants search for a target letter while reading for comprehension, they miss more instances if the target letter is embedded in frequent function words than in less frequent content words. This phenomenon, called the missing-letter effect, has been considered a window on the cognitive mechanisms involved in the visual processing of written language. In the present study, one group of participants read two texts for comprehension while searching for a target letter, and another group listened to a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In effect, similar psycholinguistic processes operate during oral comprehension and reading, no doubt because reading, aside from the necessity for print-to-sound and print-to-meaning conversions, is built upon oral comprehension skills. In a recent study, we asked one group of participants to read texts for comprehension while searching for a target letter and another group to listen to narrations of the same texts while listening for the corresponding target letter’s phoneme (Saint-Aubin, Klein, Babineau, Christie, & Gow, 2016). In the listening task, we observed a large “missing-phoneme effect”: Participants missed more phonemes embedded in function than in content words, even after we controlled for acoustic factors that covaried with word class.…”
Section: An Analogous Missing-phoneme Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…In effect, similar psycholinguistic processes operate during oral comprehension and reading, no doubt because reading, aside from the necessity for print-to-sound and print-to-meaning conversions, is built upon oral comprehension skills. In a recent study, we asked one group of participants to read texts for comprehension while searching for a target letter and another group to listen to narrations of the same texts while listening for the corresponding target letter’s phoneme (Saint-Aubin, Klein, Babineau, Christie, & Gow, 2016). In the listening task, we observed a large “missing-phoneme effect”: Participants missed more phonemes embedded in function than in content words, even after we controlled for acoustic factors that covaried with word class.…”
Section: An Analogous Missing-phoneme Effectmentioning
confidence: 99%
“…Each dot represents the two omission rates for the same target-containing word contributed by different groups of participants who read and listened, respectively. Reprinted from "The Missing-Phoneme Effect in Aural Prose Comprehension," by J. Saint-Aubin, R. M. Klein, M. Babineau, J. Christie, andD. W. Gow, 2016, Psychological Science, 27, p. 1023.…”
Section: An Analogous Missing-phoneme Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this difference could be called upon to account for the omission rate difference across experiments, such an explanation is unlikely. In effect, previous studies have shown a similar omission rate in a condition in which one function word was repeated multiple times and compared with multiple content words and in a condition in which multiple occurrences of one function word were compared with multiple occurrences of one content word (see, e.g., Saint-Aubin et al, 2003, 2016). Instead, the difference is likely to be due to differences between the two texts such as text complexity or to the implemented controls.…”
Section: Discussionmentioning
confidence: 77%
“…To investigate the possibility of finding an aural analog to the missing-letter effect while overcoming the issues found in earlier studies by Schneider et al (1989Schneider et al ( , 1991, Saint-Aubin et al (2016) presented the narration of a text lasting 2-3 min with many occurrences of the target phoneme. Participants were asked to listen for comprehension and to press a button every time they detected a given phoneme.…”
mentioning
confidence: 99%